Experiences of death preparedness among family caregivers of terminal patients: a systematic review and meta-synthesis - Xinyu Ju; Yujin Zhang; Xiaosong Wang; Qiong Lu; Yuan Li; Jinhua Hong (Frontiers in Public Health, 2026)
Background Death preparedness is an important component of hospice care, yet research focusing on family caregivers of terminally ill patients remains in its early stages, with few studies systematically synthesizing the death preparedness experiences of this group. The study aimed to integrate the experiences of death preparedness among family caregivers of terminally ill patients and provide a reference for developing family-centered supportive care interventions for this population. Methods A systematic review and meta-synthesis of qualitative studies were conducted. Six databases (PubMed, Web of Science, Embase, CINAHL, PsycINFO, and Cochrane Library) were searched for relevant qualitative studies published from database inception to January 31, 2026. We utilized the Australian JBI Quality Assessment Criteria for Qualitative Research to evaluate the quality of the included studies and utilized thematic analysis approach for data analysis. Presentation of this synthesis adhered to the PRISMA guideline. Results A total of 13 studies were included. Ten new categories were generated and synthesized into four integrated findings, including reconstructing the spiritual meaning of death, information communication for death preparation, coping with multidimensional pressures of reality, and internal and external resources to support caregivers. Conclusion Death preparedness among family caregivers of terminal patients is a complex and multidimensional psychosocial process. Its complexity and challenges need to be fully assessed and understood through the authentic experiences of family caregivers themselves. This meta-synthesis may help healthcare professionals develop family-centered clinical support measures, thereby promoting the development of hospice care practice and improving the quality of care.